PROFIL PSY-5 SCALES DARI MMPI-2 ADAPTASI INDONESIA PADA MAHASISWA SEMESTER 1 TA 2013/2014 FAKULTAS KEDOKTERAN UNIVERSITAS SAM RATULANGI MANADO - Raintama, Marsevino; Kandou, Lisbeth F. J.; Kairupan, Barnabas H. R. (e-CliniC, 2016)
Abstract: A college student is constantly facing problems from internal source as well as external source that can affect both academic and non-academic field. Those problems can disturb the student?s mental health. One of the methods to identify a person?s mental status is a personality test. This study used Personality Psychopathology Five (PSY-5) scales from the Indonesian adaptation of MMPI-2 to obtain the mental status of college students of 1st semester academic year of 2013/2014 Medical Faculty University of Sam Ratulangi. This was a descriptive study with a cross sectional survey. The results showed that of 101 respondents based on the socio-demographic the majority were females (72.28%), aged 18 years (88.12%), originated from Sulawesi Utara (64.36%), belonged to a tribe from out of Sulawesi (53.47%), had a sibling (33.67%), first child of the family (40.59%), and parents worked at the private sector. The distribution based on the academic characteristics of the respondents showed that the majority applied with the T2 and had high prestation index varied from ordinary to high (32.68% to 33.66%). Based on the distribution of Psy-5 scales of 101 respondents, there were some PSY-5 sub-scales that had high values as follows: AGGR (5.94%), PSYC (6.93%), DISC (7.92%), NEGE (12.87%), and INTR (16.83%). College students with high values of PSY-5 scales could show particular types of personality that varied in every PSY-5 sub-scales. It is suggested that students who had high scale values should be paid attention from the head of the faculty to prevent the occurence of mental disorders.Keywords: personality test, PSY-5 scales, MMPI-2, college students Abstrak: Mahasiswa cenderung berhadapan dengan masalah baik yang berasal dari sumber internal maupun eksternal, yang dapat memengaruhi prestasi bidang akademis maupun non-akademis. Setiap masalah tersebut dapat menimbulkan pengaruh pada kesehatan mental mahasiswa. Salah satu cara untuk mengidentifikasi status mental seseorang ialah dengan menggunakan tes kepribadian. Penelitian ini menggunakan Personality Psychopathology Five (PSY-5) scales dari MMPI-2 adaptasi Indonesia untuk mengetahui status mental dari mahasiswa semester 1 TA 2012/2013 FK UNSRAT. Jenis penelitian ialah deskriptif dan dilakukan survei secara potong lintang. Hasil penelitian memperlihatkan 101 responden berdasarkan sosio-demografik terbanyak ialah perempuan (72,28%), usia 18 tahun (88,12%), asal daerah Sulawesi Utara (64,36%), suku di luar Sulawesi (53,47%), jumlah bersaudara 2 orang (33,67%), anak pertama dalam keluarga (40,59%), dan pekerjaan orang tua sebagai pekerja swasta (43,56%). Distribusi berdasarkan karakteristik akademis didapatkan dari 101 responden terbanyak mengikuti jalur T2 dan memiliki nilai indeks prestasi SMA sedang dan baik (32,68% dan 33,66%). Simpulan: Pada distribusi skala Psy-5 dari 101 responden ditemukan beberapa sub skala PSY-5 yang tinggi antara lain AGGR (5,94%), PSYC (6,93%), DISC (7,92%), NEGE (12,87%), dan INTR (16,83%). Mahasiswa dengan skala PSY-5 yang tinggi didapati beberapa jenis kepribadian khas yang berbeda-beda pada tiap sub skala PSY-5. Bagi setiap mahasiswa yang menunjukkan profil skala yang tinggi seharusnya mendapat perhatian dari pimpinan fakultas untuk mencegah tmbulnya gangguan jiwa. Kata kunci: tes kepribadian, PSY-5 scales, MMPI-2, mahasiswa